Vascular plants of forest dividing-lines analyzed in respect of forest complex synanthropisation - Myśliwy, Monika (Biodiversity: Research and Conservation, 2008)
This multi-faceted analysis of the flora of forest dividing-lines is aimed at estimating their role in the process of synanthropisation. In contrast to typical forest roads, effects of forest dividing-lines on floristic changes within forest complexes seem to be moderate. The microhabitats connected with forest dividing-lines allow numerous non-forest species to grow and spread in forest complexes. This applies first of all to the species characteristic of meadows of the class Molinio-Arrhenatheretea, heatlands and clear-cut areas (Nardo-Callunetea, Epilobietea), xerothermic grasslands and fringe communities (Festuco-Brometea, Trifolio-Geranietea), sandy grasslands (Koelerio glaucae-Corynephoretea canescentis), and ruderal communities (Stellarietea, Artemisietea). Due to the low intensity of human pressure, only few of all the anthropophytes occurring presently in the Barlinek-Gorzów Landscape Park were noted on forest dividing-lines, and most of them do not invade forest communities. The distribution of some of them in the Park is clearly connected with this type of habitats (e.g. Juncus tenuis, Oxalis fontana). Dividing-lines as habitats have numerous features in common and show no distinct differentiation, regardless of the neighbouring forest communities. The vast majority of the species are not associated with a particular single forest type, nor are they limited to 2 related types, but appear across a range of forest types. A constancy of 50% or higher was recorded only in species with a generally low number of records.